PENDUSTAAN MANUSIA TERHADAP ALLAH: ANALISIS HADIS BUKHARI NO. 4974 - Ulia Fitriani, Wan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2023)
Human’s lying and insulting to God is inappropriate because human lives at God’s mercy. God is the most perfect being in which He is the only being (one), does not need any other existence and has dominion over All things. The Qur’an and hadith carry various news in which it tells about the greatness of Allah and his power that sometimes still doubted by some people such as people who doubt life after death even though before creation, the condition of man who was still in the form of origin (land) was a form of the first death of human. Among the main points in this article is talk about faith and monotheism, where the statement that Allah has broken His promises is a lie and the accusation that he took a son is an insult. With the Qur’an and hadith as the foundation for breaking every accusation that is thrown to Allah, it is impossible to think that it can be in God’s substance, and when someone can understand it as well, it can have a big impact on their faith and deliver a big love to their only one God. This research was conducted using the qualitative method, which entailed gathering data from various sources, connecting the data, and then using the data as a foundation to deny all lying and amplifying that thrown to Allah and as a foundation that Allah was the truth, and and only God all of time.